If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + 1) = 15 Reorder the terms: 2(1 + 3x) = 15 (1 * 2 + 3x * 2) = 15 (2 + 6x) = 15 Solving 2 + 6x = 15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 6x = 15 + -2 Combine like terms: 2 + -2 = 0 0 + 6x = 15 + -2 6x = 15 + -2 Combine like terms: 15 + -2 = 13 6x = 13 Divide each side by '6'. x = 2.166666667 Simplifying x = 2.166666667
| 4m+6n-8+(8m-3)= | | -19=x-11 | | X=3-6*3+2 | | -4y-1=-17.25 | | x+1/2x+4+4x= | | q^2+3z-40=0 | | -x(5x+2)=0 | | 4n^3-2n= | | X=3p+27 | | 2x^2-1-10=0 | | 3[7-2(j-8)]=4j+2 | | -12x+2=2x-166 | | m+38=-44 | | 0.3x-8=25 | | x-4sqrt(x)-12=o | | 1/3x+2/3x+9x= | | 7x+2x(4-3x)=15-6x(x-5) | | -2a-9=3 | | x-4sqrtx-12=o | | 0.4x+2.5=3.9+1.3x | | -2+11=12x-5-11x | | y+22*7+y+44*4=11 | | n(s)=0.005s^2+0.007s-0.031 | | 20+5u+10u-20-14u=1u | | Y=-6(3) | | 12.5k=17.5 | | 4-4sin(5)= | | 23=0.6h-7 | | 3n^2-9n-120= | | 9x+4y=-18 | | Y=-6(-2) | | -10=x-a |